2005
DOI: 10.1007/s00024-004-2668-1
|View full text |Cite
|
Sign up to set email alerts
|

A Simplified Approach to Earthquake Risk in Mainland China

Abstract: There are limitations in conventional earthquake loss procedures if attempts are made to apply these to assess the social and economic impacts of recent disastrous earthquakes. This paper addresses the need to develop an applicable model for estimating the significant increases of earthquake loss in mainland China. The casualties of earthquakes were studied first. The casualties of earthquakes are strongly related to earthquake strength, occurrence time (day or night) and the distribution of population in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
12
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 8 publications
(7 reference statements)
0
12
0
Order By: Relevance
“…Linear models are the most constantly used methods for assessing feature correlation [3]. In reference [4], the research has given the relationship between human losses and factors such as population density and the intensity and magnitude of the earthquakes based on the linear models. Nevertheless, due to the uncertainties and fuzziness in the data of the factors [5], integrated ensemble models were proposed and applied to the feature importance assessment models [6][7][8][9] for the purpose of improving accuracy and generalization ability of the traditional linear models [10].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Linear models are the most constantly used methods for assessing feature correlation [3]. In reference [4], the research has given the relationship between human losses and factors such as population density and the intensity and magnitude of the earthquakes based on the linear models. Nevertheless, due to the uncertainties and fuzziness in the data of the factors [5], integrated ensemble models were proposed and applied to the feature importance assessment models [6][7][8][9] for the purpose of improving accuracy and generalization ability of the traditional linear models [10].…”
Section: Introductionmentioning
confidence: 99%
“…The regularity of people's working and resting time makes the differences of earthquake occurrence time have a great impact on the fatalities [4,13]. Time was divided into two parts of this study: daytime (7:00-21:00) and sleeping time (21:00-next7:00).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…There is less agreement on the role that sociodemographic factors such as popula tion density, economic status, and level of education play in earthquake vulnerability. Higher population density is generally considered to place a community at greater risk (Samardjieva and Badal, 2002;Badal, VazquezPrada and Gonzalez, 2005;Chen, Mi and Huang 2005); however, in a study of mortality in major earthquakes world wide since 1980since , Gutierrez et al (2005 found that risk was greatest in lesspopulated rural areas. Studying the 1988 earthquake in Armenia, Armenian, Melkonian and Hovanesian (1998) found a statistically significant relationship between a low level of education and mortality.…”
mentioning
confidence: 99%